Short hospitalization period with elastic stable intramedullary nails in the treatment of femoral shaft fractures in school children - Nascimento, Fabiano Prata (Springer Berlin Heidelberg, 2010)
PURPOSE: To evaluate the safety and period of hospitalization of the treatment of femoral shaft fractures with titanium elastic nails (TEN) in the age range 5 to 14 years. The hypothesis was that TEN might be a low-cost treatment, with good clinical results and short length of hospitalization. METHODS: Thirty children with femur fractures were surgically treated with TEN. RESULTS: The patients spent an average of 9.4 days in hospital. The average period for the healing process was 7.7 weeks. Partial weight bearing was permitted 3.3 weeks after surgery. The incidence of overgrowth was 60%, with an average of 0.40 cm. CONCLUSIONS: The surgical method brings few complications and results in good limb alignment, with a short period of hospitalization and early return to daily activities and school.